Study of efficacy of mifepristone as inducing agent for mid trimester medical termination of pregnancy in women with previous cesarean section - Chikkagowdra, Shaila; Doddaiah, Vanaja; CM, Veerendrakumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Second trimester pregnancy induction in the scenario of a prior caesarean birth has become an increasingly common due to improved prenatal screening methods. The objective of this study was to evaluate efficacy of Mifepristone as inducing agent for mid trimester medical termination of pregnancy in women with previous cesarean section. Methods: Mifepristone 200 mg orally was given to 37 women willing for abortion between 13 to 20 weeks of gestation with previous LSCS for various indications during study period. After 36 hour misoprostol/oxytocin was given. Outcomes like rate of complete abortion, rupture, induction abortion interval and side effects were noted. Results: Mean induction abortion interval (IAI) was 8.2+/- 3.8 hours.80% of cases between 13 to 16 weeks aborted within first 10 hours. None of the cases had incomplete abortion, rupture or significant side effects. Conclusions: Combination regimen has abortion rate as higher as 99-100% and median induction to abortion interval is as low as 6 hours. Second trimester abortion in prior cesarean section women should be carried out with caution.